Bad money - Davis, L. J. (New American Library, 1983)
A woman in the aggressively male world of the City fights to keep her marriage, family, and job together while taking on the role of undercover investigator for the Treasury.Mary Kersey has burst through the glass ceiling. She has a high-profile City job giving strategic advice to banks. She’s the family breadwinner, a loving wife and a caring mother to Gracie, and she struggles to find the right balance between her work and her home life. Her two worlds collide when the Treasury asks Mary to take on a secret role investigating hedge funds. She knows that the company her firm is working with was acquired after manipulation of the share price plus help from a dodgy hedge fund. She finds herself torn every which way as husband, daughter, boss, and her own conscience all clamor for her attention.